Spirituality and Performance in Organizations: A Literature Review - Karakas, Fahri (Journal of business ethics, 2010)
The purpose of this article is to review spirituality at work literature and to explore how spirituality improves employees’ performances and organizational effectiveness. The article reviews about 140 articles on workplace spirituality to review their findings on how spirituality supports organizational performance. Three different perspectives are introduced on how spirituality benefits employees and supports organizational performance based on the extant literature: (a) Spirituality enhances employee well-being and quality of life; (b) Spirituality provides employees a sense of purpose and meaning at work; (c) Spirituality provides employees a sense of interconnectedness and community. The article introduces potential benefits and caveats of bringing spirituality into the workplace; providing recommendations and suggestions for practitioners to incorporate spirituality positively in organizations.